Antecedents to conspicuous consumption of luxury fashion goods by middle-income black South Africans - Mthombeni, Lebohang (My University, 2021)
South Africa is increasingly becoming an important market for luxury goods brands. This is mainly due to the country’s growing middle-income consumer segment which is considered to be upwardly mobile. As a result, South Africa has become an attractive destination for luxury goods brands. Signalling theory suggests that luxury brands – in consumer goods categories such as clothing and cars, are perceived as status symbols and consumed for their status credentials. Furthermore, there is adequate literature claiming that black South Africans exhibit a heightened interest in conspicuous consumption compared to other racial groupings. However, there is limited research addressing the factors driving middle-income black South Africans to consume luxury fashion brands conspicuously. Therefore, there was a need for this study to generate new knowledge in this area of research. Consequently, this study was concerned with investigating the antecedents to conspicuous consumption of luxury fashion goods by middle-income black South Africans. This study employed a survey questionnaire approach and a quantitative methodology for primary data collection. Data was gathered from a sample of 182 respondents across South Africa and analysed using structural equation modelling (SEM) through SPSS and Mplus software. Confirmatory factor analysis (CFA) was used to test model fit as well as reliability and validity of measurement instruments while path modelling was used to test hypotheses adopted by this report. Five (5) of the eight (8) hypotheses in this study were supported by statistical results; although, three (3) hypotheses were not supported. Among the major findings made by this report was that social class signalling (SCS) positively influenced conspicuous consumption (CC) while conspicuous consumption (CC) was not predicted by status consumption (SC). This study concluded that conspicuous consumption of luxury fashion goods by middle income black South Africans was motivated by social factors. This report’s key recommendations were for marketing professionals to imbue overt status cues in their brand campaigns to drive consumption of luxury fashion goods. Future studies could investigate whether or not the findings of this study are applicable across racial demographics in South Africa.
A research report submitted in fulfilment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, 2022
Keywords: Conspicuous consumption; Luxury; Fashion; Middle-income; Black South Africans; SDG-8: Decent work and economic growth